2021
DOI: 10.21608/eos.2021.84086.1021
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of maxillary canine impaction in an Egyptian population: a retrospective study

Abstract: Objective: To determine the prevalence of maxillary impacted canines in Egyptian population and its relativity to gender, location, and side distribution. Materials and methods: Retrospective cross-sectional study of 7730 digital panoramic radiographs collected from Alexandria city in Egypt. The sample was examined for the presence of maxillary impacted canines. The radiographs were selected from the records of several private dental clinics and the archive of a radiographic center. Results: Among the panorami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…The present study demonstrates that patients with unilateral impacted maxillary canines (82.1%) were higher than those with bilateral impaction (17.9%). These findings are consistent with majority reported by other studies [12,13,15,18]. However, no significant difference in the prevalence of right or left canine impaction in the analysed data.…”
Section: Disscusionsupporting
confidence: 93%
See 4 more Smart Citations
“…The present study demonstrates that patients with unilateral impacted maxillary canines (82.1%) were higher than those with bilateral impaction (17.9%). These findings are consistent with majority reported by other studies [12,13,15,18]. However, no significant difference in the prevalence of right or left canine impaction in the analysed data.…”
Section: Disscusionsupporting
confidence: 93%
“…Prevalence of impacted maxillary canines among genders was comparable to other studies reported in literature [4,5,10,12]. In females was 3.1%, whereas in males 0.9% with significant association between gender and canine impaction (P < 0.05), indicating that females have higher prevalence of permanent maxillary canine impaction than males.…”
Section: Disscusionsupporting
confidence: 86%
See 3 more Smart Citations